IDENTIFICATION OF THRESHER MAINTENANCE MECHANISMS IN A PALM OIL PROCESSING PLANT AT PT. BEURATA SUBUR PERSADA (BSP), NAGAN RAYA - Ahmad Arafi; Riza Ulhaq; Abdiel Khaleil Akmal; Fajar Okta Widarta (Barkah Publishing, 2026)
In the era of globalization, industrial development requires companies to maintain efficient and sustainable production systems. One of the critical components in palm oil processing is the thresher machine, which functions to separate fruits from fresh fruit bunches (FFB). This study aims to analyze the maintenance mechanism of the thresher machine at PT. Beurata Subur Persada using a qualitative descriptive approach. Data were collected through interviews, direct observations, and literature studies. The results show that the thresher machine plays a vital role in ensuring the continuity of the production process, and its performance is highly dependent on proper maintenance practices. The company implements a preventive maintenance system consisting of routine, weekly, monthly, and annual activities, including inspection, cleaning, repair, and component replacement. These maintenance practices have proven effective in improving machine reliability, extending component service life, and minimizing unexpected failures. However, several challenges remain, such as component wear, potential leakage, and insufficient maintenance documentation. Therefore, improvements in maintenance management, including systematic recording, enhanced monitoring, and workforce training, are necessary to optimize machine performance. Overall, effective preventive maintenance contributes significantly to operational efficiency and sustainability in palm oil production.